A Multi-Band Stacked RF Energy Harvester With RF-to-DC Efficiency Up to 84 - Kuhn, Veronique; Lahuec, Cyril; Seguin, Fabrice; Person, Christian (IEEE transactions on microwave theory and techniques, 2015)
The aim of this paper is to show the possibility to harvest RF energy to supply wireless sensor networks in an outdoor environment. In those conditions, the number of existing RF bands is unpredictable. The RF circuit has to harvest all the potential RF energy present and cannot be designed for a single RF tone. In this paper, the designed RF harvester adds powers coming from an unlimited number of sub-frequency bands. The harvester's output voltage ratios increase with the number of RF bands. As an application example, a 4-RF band rectenna is designed. The system harvests energy from GSM900 (Global System for Mobile Communications), GSM1800, UMTS (Universal Mobile Telecommunications System) and WiFi bands simultaneously. RF-to-dc conversion efficiency is measured at 62% for a cumulative -10-dBm input power homogeneously widespread over the four RF bands and reaches 84% at 5.8 dBm. The relative error between the measured dc output power with all four RF bands on and the ideal sum of each of the four RF bands power contribution is less than 3%. It is shown that the RF-to-dc conversion efficiency is more than doubled compared to that measured with a single RF source, thanks to the proposed rectifier architecture.